The level of university student violence from the viewpoint of university students - AL-Momani, Mohammad Omar; Rababa, Elham Mahmoud (Kultura-Społeczeństwo-Edukacja, 2023)
This study aimed at revealing the level of university violence among university students and its relationship to the variables of gender and type of specialization. In order to achieve the objectives of the study, a measure of university violence was built, as the descriptive approach was used. The study sample consisted of 2000 undergraduate students, randomly selected. The results of the study showed that the level of university violence among students was low as a whole, and in all its fields. The results also showed that the study variables contributed to explaining university violence.